1978
DOI: 10.1007/bf00353711
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dichlorvos (DDVP) inhalation on the activity of acetylcholinesterase in the bronchial tissue of rats

Abstract: The experiments presented here deal with the effects of the inhalation of dichlorvos [dimethyl-(2,2 dichlorvinyl)-phosphate, DDVP] vapor on acetylcholinesterase (ACHE) activity in rat bronchial tissue. Exposure to DDVP concentrations of 0.8 and 1.8 micrograms/l for 3 days reduced ACHE activity in the bronchial tissue (62.8 +/- 0.8 and 51.6 +/- 1.6% of the control), but did not elicit any changes in blood ACHE activity (101 +/- 4.5% of the control each). Higher concentrations (4.3 micrograms/l) induced a declin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The predominant mode of DDVP toxicity is by inhibition of cholinesterase, like other organophosphates (Reuber, 1981;DiGiacomo et al, 1987;Pauluhn et al, 1987;Schmidt et al, 1979;Ecobichon, 1991). Thus, they cause signs of toxicity including those resulting from stimulation of the muscarinic receptors of the parasympathetic autonomic nervous system (increased secretions, bronchoconstriction, miosis, diarrhea, urination, bradicardia) (Aas et al, 1987;Ecobichon, 1991).…”
Section: Lower Doses Of Dichlorvos Revealed No Electromyographic Chanmentioning
confidence: 95%
See 2 more Smart Citations
“…The predominant mode of DDVP toxicity is by inhibition of cholinesterase, like other organophosphates (Reuber, 1981;DiGiacomo et al, 1987;Pauluhn et al, 1987;Schmidt et al, 1979;Ecobichon, 1991). Thus, they cause signs of toxicity including those resulting from stimulation of the muscarinic receptors of the parasympathetic autonomic nervous system (increased secretions, bronchoconstriction, miosis, diarrhea, urination, bradicardia) (Aas et al, 1987;Ecobichon, 1991).…”
Section: Lower Doses Of Dichlorvos Revealed No Electromyographic Chanmentioning
confidence: 95%
“…Earlier studies have shown that inhalation of the organophosphate dichlorvos potently inhibits the AChE of the rat in the respiratory system and diaphragm (Pauluhn et al, 1987;Schmidt et al, 1979). Williams et al have shown that exposure to multiple low doses of organophosphates produces additive inhibition of acetylcholinesterase .…”
Section: Effects Of Dichlorvos On Respiratory System 205mentioning
confidence: 97%
See 1 more Smart Citation